Studi Tentang Candi Ngetos Di Kabupaten Nganjuk Ditinjau Dari Kajian Ikonografi - Yatmin; Zainal Afandi (Universitas Nusantara PGRI Kediri, 2022)
Study About Ngetos Temple in Nganjuk Regency, Research, Historical Education, FKIP UNP Kediri. In Indonesia many historical relics have a very extraordinary value, the temple is the result of the nation's culture that is high in value. The existence of a temple is not yet known to the wider community. Such conditions are caused by the lack of written sources about the history of the temple building. We all certainly realize that the temple building is a potential asset of the nation in various aspects of development. One of the temples that is not yet known to the wider community is Ngetos Temple. The author deliberately raised Ngetos Temple as a research object whose purpose was to study and uncover the existence of Ngetos Temple in Ngetos Village, Ngetos subdistrict, Nganjuk Regency. Ngetos area is indeed suitable for a monumental sacred building that is located in a mountainous area and allows for the development of tourist attractions of the Nganjuk regency. The results of Majapahit culture have also been studied by the Dutch East Indies government under the leadership of Governor-General Thomas Stanford Raffles since 1817. The building of Ngetos temple as a result of Majapahit culture serves as a place of worship of ancestral spirits and worship of the gods.